2005
DOI: 10.1002/ijc.21318
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression profiling identifies maspin and stathmin as potential biomarkers of adenoid cystic carcinoma of the salivary glands

Abstract: Adenoid cystic carcinoma (ACC) is one of the most common malignant tumors of the salivary glands. It tends to grow slowly but is associated with a poor prognosis compared to other malignant salivary gland tumors. To identify specific markers of ACC, we examined protein expression profiling in ACC xenograft and normal salivary glands (NSG) using fluorescent 2-dimensional differential in-gel electrophoresis (2-D-DIGE), an emerging technique for comparative proteomics, that improves the reproducibility and reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…The loss of maspin has been reported with poor prognosis in breast cancers, oral squamous cell carcinoma, lung, and prostate carcinoma (7,13). In accordance with previous studies (20,21), the results of this study showed inverse significant association between maspin expression and histologic grade. No significant correlation was found between maspin expression and lymph node metastasis, which was similar to Ghazy et al's study (22), but in contrast to the findings of Schwartz et al (23).…”
Section: Discussionsupporting
confidence: 91%
“…The loss of maspin has been reported with poor prognosis in breast cancers, oral squamous cell carcinoma, lung, and prostate carcinoma (7,13). In accordance with previous studies (20,21), the results of this study showed inverse significant association between maspin expression and histologic grade. No significant correlation was found between maspin expression and lymph node metastasis, which was similar to Ghazy et al's study (22), but in contrast to the findings of Schwartz et al (23).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the function of glandular epithelium is important for the establishment of pregnancy. Since stathmin localization has been reported in a number of secretory glands, including salivary gland (Nakashima et al 2006), mammary gland Figure 8 Effect of stathmin knockdown on the proliferation of cultured endometrial stromal cells. Stromal cells were transfected with stathmin siRNA or an irrelevant control siRNA (stathmin siRNA(K)) and cultured for 24 and 48 h, after which the proliferation rate of the cells was assayed by using the WST-1 reagent (B).…”
Section: Discussionmentioning
confidence: 99%
“…We did proteomic profiling of NOKs and OSCCderived cell lines (HSC-2 and HSC-3) using fluorescent 2D-DIGE and MALDI-TOF-MS fingerprinting in triplicate as described previously (9). Each protein extract (50 Ag) was used for the 2D-DIGE analysis.…”
Section: Methodsmentioning
confidence: 99%